THE USE OF SONG, SOCIAL MEDIA, AND GAMES IN IMPROVING VOCABULARY: STUDENTS’ PERCEPTION - Kelendonu, Rimanuella Sabathiana; Katemba, Caroline Victorine (TELL - US JOURNAL, 2023)
Vocabulary is one of the crucial aspects of learning English. However, knowing and remembering the vocabulary is difficult because there are many words in the language. The goal of this research is to know which platform will help students to improve their vocabulary more quickly. This study also seeks to answer to the research questions: 1. What is students’ perception of improving vocabulary from songs, social media, and games? 2. Which platform do students like and enjoy using to improve their vocabulary? 3. Which gender prefers to use songs, social media, and games to improve their vocabulary? 4. From songs, social media, and games. Which one that students struggle with or do not like using it? The research is designed with interview and questionnaire design. 100 students of grade 10 senior high schools from four island in Indonesia. The questionnaire was distributed online to the students and a followed up interview. The findings of this study indicate that learning through song, games, and social media can help students improve vocabulary.